2007
DOI: 10.1007/s10551-007-9565-3
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Whistleblowing Policies: Making Employees Responsible or Liable?

Abstract: whistleblowing, moral autonomy, ethical distance, moral agency,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 35 publications
2
37
0
3
Order By: Relevance
“…In this sense, whistleblowers and legislation protecting them can be regarded as the embodiment of that positive right. However, as we argued earlier and elsewhere (Tsahuridu and Vandekerckhove, 2008) this positive right as a demand of society on organizations might very well imply positive duties on whistleblowers. These positive duties reflect society's demand on whistleblowers to warn it (demand ten) and the demand by organizations on whistleblowers to warn its management (demand eleven).…”
Section: Duties and Rights In Whistleblowingmentioning
confidence: 63%
See 2 more Smart Citations
“…In this sense, whistleblowers and legislation protecting them can be regarded as the embodiment of that positive right. However, as we argued earlier and elsewhere (Tsahuridu and Vandekerckhove, 2008) this positive right as a demand of society on organizations might very well imply positive duties on whistleblowers. These positive duties reflect society's demand on whistleblowers to warn it (demand ten) and the demand by organizations on whistleblowers to warn its management (demand eleven).…”
Section: Duties and Rights In Whistleblowingmentioning
confidence: 63%
“…It is also important to be able to clearly and accurately identify all those who know and ought to have known, something that is difficult in organizations. If a positive duty to blow the whistle would be imposed, it follows that the individual would have the burden of proving his or her ignorance of the wrongdoing (Tsahuridu and Vandekerckhove, 2008). Let us suppose a situation in which employees would have a civil liability for workplace malpractice in relation to health and safety regulations.…”
Section: Specifying Who Should Knowmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Vandekerckhove and Commers (2004) use the descriptive research to argue how the debate around loyalty was a mistaken one. Also, descriptive ethics research is used to provide complexity to normative prima facie positions on whether whistleblowing is a right or a duty, and what the implications are for implementing such policies (Tsahuridu & Vandekerckhove, 2008;Vandekerckhove & Tsahuridu, 2010).…”
Section: The Impact Of the Situationmentioning
confidence: 99%
“…Hassink et al (2007) found that a substantial number of internal whistleblowing policies used wording which suggested that raising a concern is compulsory and employees might be held accountable for failing to do doing so. Tsahuridu and Vandekerckhove (2008) and Vandekerckhove and Tsahuridu (2010) have further theorised on this.…”
Section: Section 2: Frameworkmentioning
confidence: 99%